Student's Perception on the Use of English Online Learning Platforms in Tanjung Balai - Resty Wahyuni; Maydilla Sari Claudia (English Teaching and Linguistics Journal (ETLiJ), 2022)
This research was aim to analysis how is student’s perception on the use of english online learning platforms in tanjungbalai and to know does Quipper helps the students in english online learning in the Covid-19 Pandemic. In this research technique of collecting data researcher used observation and interview method. The source of data in this reseach is students in Senior Highschool 1 Tanjungbalai was focused on eleventh grade with gave 15 questions to interview the students using WhatsApp. The researcher instrument of this studey is researcher self. This study was applied qualitative design. The technique of analyzing data researcher used three steps, there are 1) Data Reduction, 2) Data display, and then 3) conclusion/verifocation. The findings from the data analysis, the student’s give negative perception on English online learning because not easier, but english online learning give positive impact such as: be independent attitude, and add the motivation to them. In using Quipper in English online learning the students give perception because the explanation in Quipper is video form so the students enjoy and understand, but they help problems in internet quota and network in using Quipper so the students sometimes difficult in using Quipper.